Azithromycin-Induced Thrombocytopenia: A Rare Etiology of Drug-Induced Immune Thrombocytopenia - Muhammad Umer Butt; Ahmad Jabri; Samy Claude Elayi (Case Reports in Medicine)
Drug-induced thrombocytopenia requires a high suspicion for diagnosis and a broad investigation to exclude other etiologies of low platelets. Cessation of the offending agent often results in recovery of platelet counts. Many medications are known to cause a degree of thrombocytopenia. We present a rare case of severe thrombocytopenia associated with administration of azithromycin.